2016
DOI: 10.1016/j.jphotobiol.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of acetoacetate in Amadori product formation of human serum albumin

Abstract: Amadori product is an important and stable intermediate, which is produced during glycation process. It is a marker of hyperglycemia in diabetes mellitus, and its accumulation in the body contributes to microvascular complication of diabetes including diabetic nephropathy and retinopathy. In this study, the effect of acetoacetate on the formation of Amadori products and biophysical properties of human serum albumin (HSA), after incubation with glucose, was investigated using various methods. These included cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Shifts of the amide I band to lower wavenumber were observed when BSA (5–8 cm −1 ) was heated at 58–90 °C for 90–120 min, when equine serum albumin (ESA) (∼3 cm −1 ) was heated at 45–90 °C for 60 min, and when HSA (4–5 cm −1 ) was heated with Glc at 37 °C for 7–21 days . Although FTIR was performed for heated BSA with Glc and mannose (45 °C, 2 h), dextran (58 °C, 20 h) and lactobionic acid (room temperature, 48 h) in some studies, the shift of amide A band has not been reported .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts of the amide I band to lower wavenumber were observed when BSA (5–8 cm −1 ) was heated at 58–90 °C for 90–120 min, when equine serum albumin (ESA) (∼3 cm −1 ) was heated at 45–90 °C for 60 min, and when HSA (4–5 cm −1 ) was heated with Glc at 37 °C for 7–21 days . Although FTIR was performed for heated BSA with Glc and mannose (45 °C, 2 h), dextran (58 °C, 20 h) and lactobionic acid (room temperature, 48 h) in some studies, the shift of amide A band has not been reported .…”
Section: Resultsmentioning
confidence: 99%
“…Shifts of the amide I band to lower wavenumber were observed when BSA (5-8 cm −1 ) was heated at 58-90 ∘ C for 90-120 min, 56,60,61 when equine serum albumin (ESA) (∼3 cm −1 ) was heated at 45-90 ∘ C for 60 min, 62 and when HSA (4-5 cm −1 ) was heated with Glc at 37 ∘ C for 7-21 days. 63,64 Although FTIR was performed for heated BSA with Glc and mannose (45 ∘ C, 2 h), dextran (58 ∘ C, 20 h) and lactobionic acid (room temperature, 48 h) in some studies, the shift of amide A band has not been reported. 15,65,66 Shifts of the amide III band to lower wavenumber were observed when BSA was heated at 90 ∘ C for 90 min (10 cm −1 ), 60 at 100 ∘ C overnight (7 cm −1 ) 67 and at room temperature for 48 h in the presence of lactobionic acid (∼6 cm −1 ).…”
Section: Ft-ir Spectra Of Heated and Glycated Bsasmentioning
confidence: 99%
“…Although this work is focused on cell growth and metabolism, it is important to point out that LiAcAc has been used also in several other studies where the authors focused on other parameters. Some of the studies also used LiCl a control [33,34], but several others studies did not [35,36]. Most importantly, there are reports where the authors do not specify which type of AcAc salt has been used, making it difficult to evaluate if the results are based on proper controls [37,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Beside AGEs, the intermediate compounds of glycation process can also have adverse health effects. One of the important glycation intermediate products is the Amadori product, which is produced during AGE formation . The Amadori product concentration increases in the body under diabetic conditions, and is considered as a marker of hyperglycemia in diabetes mellitus .…”
Section: Introductionmentioning
confidence: 99%